Restraint use and injury in forward and rear-facing infants and toddlers involved in a fatal motor vehicle crash on a U. S. Roadway - Yu-Yun Huang; Chang Liu; Joyce C. Pressley (BMC, 2019)
Abstract Background Use of appropriate child passenger safety restraints reduces injury in infants, with rear facing restraints favored over forward facing. In 2011, the American Academy of Pediatrics (AAP) began recommending that infants and children under the age of 2 years be restrained in a rear-facing seat installed in the vehicle's rear seat. This study examines the practice of rear-facing restraints pre- and post-AAP recommendations for children under 2 years. Methods Data from the Fatality Analysis Reporting System (FARS) from 2008 to 2015 were used to examine restraint status and injuries in rear-seated infants and toddlers aged 0 to less than 2 years involved in fatal collisions (n = 4966). Subpopulation analyses were conducted on 1557 children with seat facing direction recorded. Multivariable logistic regression was used to generate odds ratios (OR) with 95% confidence intervals (CI). Covariates considered for inclusion in the multivariable model included passenger characteristics (age, gender, seating position), driver characteristics (age, gender, seat belt status, alcohol status, drug status, previous traffic violations), vehicle characteristics (vehicle type), and crash-level characteristics (day/night, weekday/weekend, rush hour, expressway/surface street, urban/rural). Results Approximately 6.7% (330 of 4996) of infants and toddlers were unrestrained with mortality that was approximately triple that of restrained infants (40.0% vs 13.7%, P < 0.0001). In multivariable adjusted models, predictors of an infant being unrestrained included unrestrained driver (OR: 3.17, 95% CI: 2.38-4.21), driver aged less than 20 years (OR: 2.18, 95% CI: 1.42-3.34), driver alcohol use (OR: 2.21, 95% CI: 1.42-3.44), center-seated infant (OR: 1.55, 95% CI: 1.19-2.03) and weekday crash (OR: 1.52, 95% CI: 1.12-2.01). Of all rear-seated children whose restraint status were reported (4966), rear-facing restraint use increased from 5.0% to 23.2% between 2008 and 2015 (P < 0.0001). The odds of rear-facing restraint use increased after introduction of the AAP guideline among infants aged 0 to < 1 year old (OR: 2.12, 95% CI: 1.46-3.10) and among toddlers aged 1 to < 2 years old (OR: 1.97, 95% CI: 1.03-3.79). Conclusion Trends in the use of rear-facing child restraints improved over the timeframe of this study, but remain low despite the introduction of AAP guidelines and the strengthening of child restraint laws.